Typology of Flat Towers in Indonesia - Sueca, Ngakan Putu (Journal of Civil Engineering, Architecture and Built Environment; Vol 1 No 1 (2017): Civil Engineering, Architecture and Built Environment, 2020)
House has become basic human needs; however this is critical problem especially in urban areas. In order to uncover housing shortages, the government has programmed to build walk up flat, due to that horizontal housing has bad following impacts. Walk up flat is possible alternative to be considered to solve existing problems. The goal of this study is to understand walk up flat typology in Indonesia. Besides that it is hoped that it can be explained dwellers’ behavior and their adaptation mechanism has been done. Qualitative method with case study approach has been used in this research. Several walk up flats in big cities in Indonesia has been selected as case studies. Observation results and study show there are many types of walk up flat in Indonesia, either in terms of ownership status, developers, number of floors, layout, dimension of floor space unit, goals of development, etc. Urban societies in Indonesia have no meaningful problems live in walk up flat. They can adapt, and able to adjust live in walk up flat. Live in walk up flat enhance their tolerance, and lower the privacy standard they enjoyed. Many social activities have been created to establish community’s sense and to improve dwellers’ capacities. Almost no considerable problem found, either in term of social live or in term of security in walk up flat. Small cases may happened, however dwellers perceive that it is common and they believe that the life will back to normal afterwards.   Keywords : walk up flat, apartment for society, cultural adaptation, Bali